Literature Review: Risk Factors of Stunting in Children Under Five Years Old and How to Prevent - Sang Ayu Kompiyang Indriyani; Amatullah, Tazkiyah Arafah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Stunting is a health problem if a child's height is not appropriate for their age, especially in developing countries, including Indonesia. UNICEF notes that two main factors causing stunting are inadequate food intake and infection. This issue is very crucial to consider because of the implications is not only short-term but also has an impact on future excellence in human resources.. This investigation aims to identify risk factors that raise the possibility of stunting in kids younger than five, and evaluate the most effective intervention in reducing the prevalence of stunting, especially in Indonesia. Using the literature review method, this study gathered information from publications in the last 10 years through databases such as PubMed and Google Scholar. The keywords that we used were ‘Stunting, Risk Factor, Under five years’. The inclusion criteria were journals that provided information about risk factors for stunting in kids younger than five and were published in Indonesian and English. Some of the research results found were various factors that have an association with stunting including economic status, maternal education, low birth weight (LBW), exclusive breastfeeding, and a history of infectious diseases in children. Numerous investigations have demonstrated that infants born with low birth weight have twice the risk of being stunted. In addition, children from low income families and with mothers who have low education levels were also more prone to stunting. Stunting prevention can be focused on exclusive breastfeeding followed by complementary feeding after 6 months of age, improving access to sanitation and health facilities, and conducting nutrition specific and nutritionsensitive interventions.